345 INTRAVENOUS CANGRELOR INFUSION IN ELDERLY PATIENTS UNDERGOING PERCUTANEOUS CORONARY INTERVENTION: A SUBANALYSIS OF THE ICARUS REGISTRY. (15th December 2022) - Benenati, Stefano; Gragnano, Felice; Capolongo, Antonio; De Sio, Vincenzo; Scalamera, Riccardo; Bertero, Edoardo; Musumeci, Giuseppe; Annibali, Gianmarco; Campagnuolo, Salvatore; Galasso, Gennaro; Silverio, Angelo; Bellino, Michele; et al.
Abstract: Aims: To assess the clinical characteristics and compare in-hospital outcomes of elderly and non-elderly patients receiving cangrelor in the peri-percutaneous coronary intervention (PCI) phase. Methods: Consecutive patients treated with cangrelor in 7 Italian institutions were retrospectively enrolled in the ICARUS ("Intravenous CAngrelor in high-bleeding Risk patients Undergoing percutaneouS coronary intervention", NCT05505591) registry. Elderly patients were defined if age was ≥75 years at the time of PCI. The primary endpoint was net adverse clinical events (NACE), defined as a composite of cardiovascular death, myocardial infarction, stroke, definite or probable stent thrombosis and Bleeding Academic Research Consortium (BARC) 2, 3 or 5 bleeding, at 48 hours. Secondary endpoints were assessed at 48 hours and throughout the hospital stay. Independent predictors of the primary endpoint were also assessed. Results: Out of 551 patients undergoing PCI with cangrelor between January 2019 and August 2022, 174 (32%) were elderly. Mean age was 81±5 vs. 61±8 years in elderly vs. non-elderly patients (p<0.001). Female sex (32% vs. 21%, p=0.006), atrial fibrillation (20% vs. 5%, p<0.001), chronic kidney disease (30% vs. 6%, p<0.001) and heart failure (14% vs. 8%, p=0.041) were more frequent in the elderly group, whereas presentation with acute coronary syndrome (ACS) was less frequent (69% vs. 83%, p=0.001). Elderly patients received shorter cangrelor infusion (122±25 vs. 134±43 minutes, p=0.001) and were more frequently administered with clopidogrel after PCI (50% vs. 19%, p<0.001). At 48 hours, elderly patients had higher rates of NACE (13% vs. 6%, p=0.006) and BARC 2, 3 or 5 bleeding (11% vs. 5%, p=0.013), whereas the rates of other 48-hour and in-hospital clinical endpoints did not differ. At multivariable analysis, age ≥75 years (odds ratio [OR] 1.07, 95% CI 1.02-1.12, p=0.004), major anemia (OR 1.10, 95% CI 1.005-1.22, p=0.038), ACS at presentation (OR 1.08, 95% CI 1.03-1.14), femoral access (OR 1.13, 95% CI 1.06-1.22) and cardiogenic shock (OR 1.35, 95% CI 1.21-1.50) independently predicted the occurrence of 48-hour NACE. Conclusions: Advanced age is a distinctive risk feature among patients receiving intravenous cangrelor in the peri-PCI phase. Elderly patients had higher rates of adverse events at 48 hours, with advanced age (≥75 years) being an independent predictor of NACE.